THE EFFECTIVENESS OF THE TALKING STICK LEARNING MODEL ON ENGLISH LEARNING OUTCOMES OF CLASS IV STUDENTS OF SD NEGERI 21 PALEMBANG - Nur Padila Maharani; Eni Heldayani (Esteem Journal of English Education Study Programme, 2024)
This thesis discusses the effectiveness of the talking stick learning model on class students' English learning outcomes IV SD Negeri 21 Palembang. This research aims to determine (1) the English learning outcomes of fourth grade students at SD Negeri 21 Palembang (2) to determine the English learning outcomes of students using the talking stick learning model (3) to determine whether the takking stick learning model is effective on language learning outcomes. English fourth grade students. This type of research is Quantitative Experimental research, namely True Experimental design with a pretest-posttest control group design, the subjects of this research are class IV students at SD Negeri 21 Palembang, the sample is class IV.B as the experimental class, and class IV.A as the control class . Based on the results of descriptive data analysis, the average score obtained for the two groups, namely the control class (pretest) was 47 and the posttest results were 69 with a difference of 23, while in the experimental class before treatment (pretest) it was 61 and after treatment (posttest) it was 85 with difference of 25. Meanwhile, based on the calculation results in the t-test calculation, the value of t_count=2.95 is obtained when compared with t_table 37, which is 1.687, meaning t_count> t_table, so Ho is rejected and Ha is accepted. So it can be concluded that the talking stick learning model is effective on the English learning outcomes of class IV students at SD Negeri 21 Palembang.